Assay Conditions and the Demonstration of Nitroimidazole Resistance in Tritrichomonas foetus - Meingassner, Josef G. (1978)
Tritrichomonas foetus KV(1), a nitroimidazole-susceptible strain, and KV(1)/M100, its nitroimidazole-resistant daughter strain, differed markedly in their in vivo susceptibility to metronidazole. In vitro susceptibility testing in multiwell plates and tubes with different trichomonad media containing no, or low concentrations of, ascorbate demonstrated that the resistant strain behaves like the susceptible one, if tested under anaerobic conditions (deep cultures in tubes or multiwell plates in anaerobic jars), but shows resistance if tested in the presence of air (multiwell plates exposed to air). In media containing high concentrations of ascorbate, no resistance was observed even in air. The results suggest that the two strains differ in the regulation of internal redox systems and underscore the role testing methods may play in the in vitro detection of nitroimidazole-resistant protozoan parasites.